Peningkatan Pengetahuan Jurnalistik Siswa SMA Kota Medan Melalui Pemanfaatan Smartphone - Corry Novrica AP Sinaga (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2019)
Smartphones make widely opportunity for us to practice the science of journalism. Anyone can cover and then spread the news. Through various social media applications,  everyone can become a reporter, deliver news to friends, spread it, and then share the news to everyone. The results of research on smartphone utilization in improving journalistic skills to 40 students of SMA Negeri 4 Medan  and 36 student of SMA Kartika I-2 Medan, the pre test showed, 95% of 10th grade students is a smartphone user with a usage period of 3 to 5 years. Because of that the students are used to taking photos and making videos with their smart phones. But its naturally is only for personal consumption and technically, the results are not good for journalistic activities. But after being given journalistic introduction training by using a smartphone, for 2 days, the post test results showed an increase in students' knowledge, about techniques for taking photos and videos of humans, objects and other moving objects, for journalistic purposes. In addition, students also recognize the existence of Citizen Journalism, citizen journalism. Key Word: Smartphone, Journalism, Students